Understanding public willingness to pay more for plant-based meat: environmental and health consciousness as precursors to the influence of presumed media influence model - Ho, Shirley S. (2022)
Expanding upon the Influence of Presumed Media Influence (IPMI) model, our study investigates prior beliefs as precursors to the IPMI model in predicting individuals’ willingness to pay more for plant-based meat. Our survey of 1,008 adult Singaporeans revealed that attention to benefit media messages on plant-based meat was positively associated with presumed others’ attention. This subsequently predicted attitudes and perceived social norms of paying more for the product which, except for descriptive norms, in turn predicted individuals’ willingness to pay more. More importantly, we found that prior beliefs–namely environmental and health consciousness–were predictive of attention to media messages on plant-based meat, indicating selective exposure to media messages. Theoretically, our findings highlight the importance of pre-existing beliefs on the IPMI model. Practically, recommendations for key stakeholders on how to enhance individuals’ willingness to pay more for the product were discussed.